SOCIO-PSYCHOLOGICAL FEATURES OF PERSONALITY FORMATION OF YOUNG LEADERS (American Journal of Pedagogical and Educational Research, 2024)
This article provides opinions on the role and importance of young leaders in the life of our country. What is a coping strategy, who introduced it to the science and how it is useful for young leaders is explained.